The Romberg sign, unilateral vestibulopathy, cerebrovascular risk factors, and long-term mortality in dizzy patients - Berge, Jan Erik; Goplen, Frederik Kragerud; Aarstad, Hans Jørgen; Storhaug, Tobias Andre; Nordahl, Stein Helge Glad (Frontiers in Neurology, 2022)
Objectives: Describe the relationship between unsteadiness, canal paresis, cerebrovascular risk factors, and long-term mortality in patients examined for dizziness of suspected vestibular origin. Study design: Observational cohort with prospective collection of survival data. Setting: University clinic neurotological unit. Patients: Consecutive patients aged 18 – 75 years examined in the period 1992 – 2004 for dizziness of suspected vestibular origin. Outcome measures: Overall survival. Standardized mortality ratio (SMR). Factors: Unsteadiness, canal paresis, age, sex, patient-reported diabetes, hypertension, heart disease, stroke, or ministroke. Patients were classified as steady or unsteady based on static posturography at baseline compared to normative values. Results: The study included 1561 patients with mean age 48 years and 60 % females. Mean follow-up was 22 years. Unsteadiness was associated with higher age, heart disease, diabetes, hypertension, and cerebrovascular dizziness. There were 336 deaths over 31,335 person-years (SMR 0.96; 95 % confidence interval: 0.86 – 1.07). Canal paresis was not related to unsteadiness (chi square: p = 0.46) or to mortality (unadjusted Cox hazard ratio: 1.04, 95% CI: 0.80 – 1.34). Unsteadiness was an independent predictor of mortality (adjusted Cox hazard ratio: 1.44, 95% CI: 1.14 – 1.82). Conclusions: Unsteadiness measured by static posturography is associated with higher age, known cerebrovascular risk factors, and with increased long-term mortality, but not with canal paresis in patients evaluated for dizziness. The study highlights the importance of evaluating patients with conspicuous postural instability for non-vestibular causes.